The Contributions of Winter Cloud Anomalies in 2011 to the Summer Sea‐Ice Rebound in 2012 in the Antarctic. Issue 6 (25th March 2019) - Wang, Yunhe; Yuan, Xiaojun; Bi, Haibo; Liang, Yu; Huang, Haijun; Zhang, Zehua; Liu, Yanxia
Abstract: Unlike the rapid decline of Arctic sea ice in the warming climate, Antarctic sea‐ice extent exhibits a modest positive trend in the period of near four decades. In recent years, the fluctuation in Antarctic sea ice has been strengthened, including a decrease toward the lowest sea‐ice extent in February 2011 for the period of 1978–2016 and a strong rebound in the summer of 2012. The sea‐ice recovery mainly occurs in the Weddell Sea, Bellingshausen Sea, Amundsen Sea, southern Ross Sea, and the eastern Somov Sea. This study offers a new mechanism for this summertime sea‐ice rebound. We demonstrate that cloud‐fraction anomalies in winter 2011 contributed to the positive Antarctic sea‐ice anomaly in summer 2012. The results show that the negative cloud‐fraction anomalies in winter 2011 related to the large‐scale atmospheric circulation resulted in a substantial negative surface‐radiation budget, which cooled the surface and promoted more sea‐ice growth. The sea‐ice growth anomalies due to the negative cloud forcing propagated by sea‐ice motion vectors from September 2011 to January 2012. The distribution of the sea‐ice anomalies corresponded well with the sea‐ice concentration anomalies in February 2012 in the Weddell Sea and eastern Somov Sea. Thus, negative cloud‐fraction anomalies in winter can play a vital role in the following summer sea‐ice distribution. Key Points: Wintertime cloud fraction anomalies in 2011 contributed significantly to the summertime sea‐ice rebound in 2012 in the Antarctic Less cloud fraction in winter 2011 related to large‐scale atmospheric circulation resulted in a strong negative surface‐radiation budget Cloud forcing in winter 2011 cooled the surface, promoted more sea‐ice growth, and resulted in more sea‐ice survival in summer 2012